Acacia and Eucalyptus plantations modify the molecular composition of density organic matter fractions of subtropical native pasture soils - dos Anjos Leal, Otávio; Santana, Graciele Sarante; Knicker, Heike; González-Vila, Francisco J.; González-Pérez, José A.; Dick, Deborah Pinheiro (Geoderma, 2024)
•Py-GC/MS confirmed stronger Eucalyptus litter recalcitrance compared to Acacia litter.•Eucalyptus modified more C and N stocks and less the chemistry of light SOM pools.•n-alkane molecular proxies in SOM pools sensitively responded to the exotic forests.•Acacia caused stronger chemical shifts in light SOM pools, mainly up to 10 cm depth.•Seven-year cycle of forests did not affect C and N stocks of heavy pool and bulk SOM. In Southern Brazil, exotic species as Acacia (A) and Eucalyptus (E) are often planted over native pasturelands and may change bulk soil organic matter (SOM) composition as verified in our previous study with Cambisols (0–5 cm). Here we aimed to follow the impact of seven-year A and E plantation on the composition of the free light- (FLF), occluded light- (OLF) and heavy fraction (HF) of SOM along the soil profile. We hypothesized that A and E may have shifted the molecular composition and carbon (C) stocks (Cs) of SOM fractions, at least at 0–5 cm; with stronger shifts caused by A due to greater E litter recalcitrance. Litter and soil samples (0–20 cm) were collected at A and E and neighboring native pasturelands without A (WA) and without E (WE). Litter, FLF, OLF and HF samples were subjected to C, nitrogen (N), pyrolysis–gas chromatography/mass spectrometry (Py-GC/MS) and lipid biomarkers analysis. In E soil, the Cs of FLF at 0–5 cm (0.5 Mg ha−1) and OLF at 5–10 cm (1.7 Mg ha−1) were 194 and 70 % greater than in WE, whereas in A soil the Cs of OLF at 0–5 cm (0.2 Mg ha−1) was 44 % lower than in WA. Nevertheless, A changed more remarkably the composition of SOM fractions, confirming our hypothesis partially, likely due to greater A litter biodegradability (<C:N ratio, <aromatic and polyaromatic and >polysaccharides abundance) compared to E. The contribution of A litter to FLF (0–10 cm) was evidenced by abundance of long chain and the predominance of odd-over-even n-alkanes (particularly >C29), and to OLF (0–20 cm) by the greatest abundance of n-alkanes at C31, resembling A litter. Loss of C and N of OLF in A compared to WA (0–5 cm) was compensated by fresh A litter additions to FLF and OLF and microbial-derived compounds association to soil minerals, equaling soil Cs in A and WA. The lower soil N stock in A compared to WA likely resulted from depletion of occluded microbial-derived N-compounds, supposedly reflecting the breakdown of soil aggregates at forest plantation. The increase of Cs in FLF and OLF of E compared to WE soil was associated with increased abundance of aromatics and n-alkane/alkenes and decrease of fatty acids. Similar patterns of n-alkanes observed for OLF of E and WE soil confirmed the incipient contribution of E litter to OLF. Conversion of these pastures to A and E modifies SOM composition and protection, requiring policies in view of the highly invasive potential and possible negative implications of A and E to native pasture regeneration.